SOCIAL DYNAMICS IN DISTRIBUTIONI AND USE OF BANTEN SET TOP BOX - April Laksana; A. Nashrudin P; Riska Ferdiana; Meiby Zulfikar (Nindikayla Institute, 2023)
After the Analog Switch Off (ASO) in the Banten Region (outside of Greater Tangerang), it turns out that there are still many problems related to the distribution and use of Set Top Boxes (STB). As part of the national television digitization program, the government has encouraged people to switch from analog to digital television by using STB. Several factors become obstacles in the distribution and use of STB in the Banten region, such as differences in income levels and limited infrastructure, socialization and information, market competition, and the different needs and preferences of the community. By knowing these social factors, it is hoped that the government and broadcasting institutions will be able to develop a more effective and efficient strategy to increase the use of STB throughout the Banten region. This paper is expected to provide information and input for policy makers to overcome obstacles to the distribution and use of STB in the region. This paper aims to identify, analyze and identify social factors that influence the distribution and use of STB as a social dynamic in the distribution and use of STB in the Regions. It is hoped that this paper can provide a better understanding of the social dynamics in the distribution and use of STB in the Banten region, and can provide information and input for the government and broadcasting institutions in formulating policies and strategies for more effective and efficient distribution and use of STB in the region. Through this paper, it is hoped that it will be able to answer the problems that occur in society as a post-ASO social dynamic and the distribution and use of STB in the Banten Region so that they can enjoy the benefits of digital television technology